High density lipoprotein with apolipoprotein C-III is associated with carotid intima-media thickness among generally healthy individuals. (February 2018) - Yamamoto, Rain; Sacks, Frank M.; Hu, Frank B.; Rosner, Bernard; Furtado, Jeremy D.; Aroner, Sarah A.; Ferrannini, Ele; Baldi, Simona; Kozakova, Michaela; Balkau, Beverley; Natali, Andrea; Jensen, Majken K.; et al.
Abstract: Background and aims: About 6–7% of high density lipoprotein (HDL) has a protein called apolipoprotein (apo) C-III that regulates lipoprotein metabolism and can provoke an inflammatory response. HDL without apoC-III is inversely associated with coronary heart disease (CHD), whereas HDL with apoC-III is directly associated with CHD. We investigated how the presence of apoC-III affects the association between HDL and early stages of atherosclerosis measured as carotid intima-media thickness (cIMT). Methods: We examined the cross-sectional associations between the apoA-I concentrations of HDL subspecies with and without apoC-III and cIMT measured by high resolution B-mode carotid ultrasonography among 847 participants from the European multi-center Relationship between Insulin Sensitivity and Cardiovascular disease (RISC) study. Results: HDL with and without apoC-III demonstrated significantly opposite associations with both cIMT indexes (p-heterogeneity of associations comparing the two subspecies was 0.002 for cIMT at common carotid artery (cIMT at CCA) and 0.006 for the maximum cIMT in any carotid segment (cIMT max)). Compared to the lowest quintile, the highest quintile of apoA-I in HDL without apoC-III was associated with 3.7% lower cIMT at CCA ( p- trend = 0.01) or 7.3% lower cIMT max ( p- trend = 0.003), while the highest quintile of apoA-I in HDL with apoC-III was associated with 4.4% higher cIMT at CCA ( p- trend = 0.001) or 7.9% higher cIMT max ( p- trend = 0.002). Total apoA-I as well as total HDL cholesterol was not associated with cIMT whereas higher levels of total apoC-III and apoC-III contained in HDL were significantly associated with higher cIMT ( p- trend<0.01). Conclusions: HDL apoC-III is a promising target for atherosclerosis prevention and treatment. Highlights: Two HDL subspecies had significantly opposite associations with cIMT. HDL that contains apoC-III was directly associated with cIMT. HDL that does not contain apoC-III was inversely associated with cIMT. Neither HDL cholesterol nor apoA-I had a significant association with cIMT. HDL apoC-III is a promising target for atherosclerosis prevention and treatment.